Intrauterine Gauze Packing in Primary Post Partum Hemorrhage following Caesarean section: A Clinical study - Yong, shao; Pradhan, M (Nepal Journal of Obstetrics and Gynaecology, 2013)
Aims: To study the effectiveness of uterine gauze packing to manage and prevent primary postpartum haemorrhage during cesarean delivery. Methods: This was a prospective study that was conducted in the department of obstetrics and gynecology, first affiliated hospital of Chongqing Medical University from Jan to May 2011. Patients included in the study were those with intractable postpartum hemorrhage not responding to medical treatment and for prevention of hemorrhage that could develop during cesarean section. Exclusion criteria included cases of ruptured uterus and vaginal deliveries.Packing was done using 2 m long and 10 cm wide sterilized gauze from the fundus through the cesarean incision with its end passing through cervix into the vagina and left for 24-48 hours or removed earlier in cases of failure to control hemorrhage. Results: Intrauterine gauze packing during cesarean section to arrest primary postpartum hamorrhage is a successful non-invasive technique. Intractable primary postpartum hamorrhage encountered in 42 (30.9%) cases had PPH after cesarean section. Placenta previa found in 48 (35.3%) cases unresponsive to uterotonics drugs was the commonest cause of uterine gauze packing. Intrauterine gauze packing was successful in 130 (95.6%) cases. Conclusions: Uterine packing is a cost effective, quick and safe procedure to manage and prevent primary PPH during cesarean delivery. Uterine packing is of benefit in achieving hemostasis particularly in cases of post partum hemorrhage due to low-lying placenta previa/accreta associated with lower segment bleeding conserving the uterus in women with cesarean delivery. Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 33-36 DOI: http://dx.doi.org/10.3126/njog.v7i1.8833